GERAKAN REMAJA DAN PEMBENTUKAN KADER PEDULI KRR BERSAMA PEMUDA/I KARANG TARUNA DESA KAPITA KEC. BANGKALA KAB. JENEPONTO - Nurhayati Nurhayati; Linda Hardianti Saputri (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
Adolescence is a transitional period between childhood and adulthood and has not yet reached the stage of mental and social maturity so that they have to face conflicting emotional and social pressures. There are so many life events that will occur that will not only determine adult life but also the quality of life of the next generation, thus placing this period as a critical period. As a first step in prevention, increasing adolescent knowledge about reproductive health must be supported by firm communication, information and education (KIE) materials. and youth counseling so that the benefits are closer because they can get information directly through the role of the youth involved in Karang Taruna. In the Activity Process, education was provided through learning videos, the provision of Pocket Books on Reproductive Health and Explanations on Reproductive Health and the formation of Youth Reproductive Health Cadres, which was attended by 21 youth youth groups, both women and men, with the hope that KRR Kapita Village cadres who came from youth and Youth Youth Organizations have the knowledge and skills in providing a good and correct understanding to young people regarding Reproductive Health. Furthermore, after the KRR Cadre was formed, a direct simulation was carried out on the groups that had been formed, there were those who played the role of teenagers who would be given education and there were those who acted as KRR Cadres who conveyed matters related to reproductive health so that the KRR Cadres could understand their role in the future in the village. Capita.